2005
DOI: 10.3102/00028312042002331
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Employment During High School: Character Building, Subversion of Academic Goals, or a Threshold?

Abstract: This study showed that working during high school had negative effects on 15 of 23 Grade 12 and postsecondary outcomes such as achievement, course-work selection, educational and occupational aspirations, and college attendance. These effects were found with control for background variables and parallel outcomes from Grades 8 and 10 based on the 8-year (four-wave), nationally representative National Education Longitudinal Survey of 1988. The only benefit of working was a reduction in postsecondary unemployment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 30 publications
3
147
1
6
Order By: Relevance
“…For example, as noted earlier, Marsh and Kleitman (2005) found that the only beneficial effect of paid work during high school was when students worked to save for college, thus using work as a means to a long-term educational goal. Moreover, the very large-scale Monitoring the Future study, with over 300,000 8th, 10th, and 12th graders, showed that individual preferences for part-time over full-time work were stronger predictors of school grades, college plans, and enrollment in college-preparatory high-school programs than actual work hours (Bachman et al 2003).…”
Section: Effects Of Working: Not Only Competing For Hours But Also Fomentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as noted earlier, Marsh and Kleitman (2005) found that the only beneficial effect of paid work during high school was when students worked to save for college, thus using work as a means to a long-term educational goal. Moreover, the very large-scale Monitoring the Future study, with over 300,000 8th, 10th, and 12th graders, showed that individual preferences for part-time over full-time work were stronger predictors of school grades, college plans, and enrollment in college-preparatory high-school programs than actual work hours (Bachman et al 2003).…”
Section: Effects Of Working: Not Only Competing For Hours But Also Fomentioning
confidence: 99%
“…An alternative skillsbuilding model claims that being involved in paid work builds skills and attitudes that are important for a reliable worker (Mortimer and Finch 1986;Schoenhals et al 1998). A combination of the school/work competition and the skills-building model is what some refer to as a threshold model (Greenberger and Steinberg 1986;Marsh and Kleitman 2005), according to which work is conducive to education and development in the lower range of hours invested, but detrimental at more than 20 h of work per week. Looking back over three decades of empirical work and drawing on more recent analyses of large-scale longitudinal data sets (NELS), Marsh and Kleitman (2005) conclude: First, paid employment during high school has negative effects on a wide range of desirable outcomes (achievement, course work selection, educational and occupational aspirations and college attendance, staying out of trouble, developing positive habits); second, these negative effects are present even at lower levels of employment (less than 10 h a week); and third, negative effects become more pronounced as the number of hours at work increases, following a linear relationship, except among those students who work to save money for college.…”
Section: Empirical Evidence Regarding Consequences Of Teenage Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo tanto, percibir altos ingresos por hora para ahorrar para la educación futura tiene un efecto positivo en el rendimiento escolar. En contraste, gastar un alto salario en salidas con los amigos y gastos como la renta y el auto son negativos para la permanencia escolar (Marsh y Kleitman, 2005). En la ENOE no se presenta información sobre el gasto que refleje las motivaciones de los estudiantes; por ello no se analizó este indicador, aunque se reconoce que pudiera ser importante como factor mediador en la relación entre salario y abandono escolar.…”
Section: El Salario De Los Estudiantes Que Trabajanunclassified
“…Se incorporó al estudio la variable del grado, que atribuyó el valor "0" a aquellos alumnos que estaban cursando el primer año de preparatoria y el valor "1" a los que cursaban el segundo año de preparatoria. Se esperó que la deserción fuera mayor en los grados menores, dado que se ha mostrado en diversos estudios que los jóvenes de reciente ingreso son más propensos a desertar en comparación con quienes están próximos a salir (Bean, 1982;Marsh, 1991;Marsh y Kleitman, 2005).…”
Section: Descripción De Las Variables De Análisisunclassified